PERS DALAM DEMOKRATISASI DI INDONESIA: Kajian Tentang Peranan Pers Dalam Peristiwa Revolusi Mei 1998 - Encep Solihutaufa (STISIP Widyapuri Mandiri, 2022)
The purpose of this paper is to find out how the role of the press in the May 1998 revolution and to find out the obstacles faced by the press in carrying out its role. This research is descriptive and literary in nature, by analyzing and describing the role of the press in the May 1998 revolution through books, journals, articles, documents and research results related to these events. The background for determining the topic of this research is considering the press as a social institution that has power in the political system and based on the author's observation that the press during the new order was always limited by the government's space for movement, in other words the government carried out strict control over the press, but in situations and circumstances Under such conditions, the press is still able to play a role in realizing democracy in Indonesia, especially in the events of the May 1998 revolution. The news that was critical during the May 1998 revolution presented by the press would undermine the legitimacy of the government regime. The press is also a means for the public to convey input into the political system. Thus, it is clear that the press has a significant role in the May 1998 revolution. The role of the press in democratization is as a means of change and as a means of control and criticism. When it comes to the May revolution, the role of the press as a means of change consists of the press as issues manager, delegitimizing the regime and as a social organizer. The obstacles experienced by the press in carrying out its role are the intervention or restraint of the government on the press and the excitement of the press by electronic media.